Studi Evaluasi Kinerja Ruas Jalan MT Haryono Kota Malang - Amal, Andi Syaiful; Alamsyah, Alik Ansyori; Darmawan, Azhar Adi (Universitas Batanghari Jambi, 2024)
The MT Haryono highway in Malang City is a type 4/2 UD collector road which connects various places in both the economic and educational sectors in Malang City. The large number of activities that occur on this road result in a buildup of vehicles and high side obstacles, causing traffic jams during rush hours. To overcome this problem, an analytical study using the MKJI 1997 method is needed. The results of the analysis are the value of the degree of saturation for current road conditions >0.80, namely 0.94 at the service level (E) of unstable flow. Therefore, 2 (two) alternatives are given to reduce the DS value, the second alternative is recommended, namely changing the road type to a one-way road so that a DS value of 0.67 is obtained at a stable flow service level (C). Analysis of the performance of the MT Haryono Road section after alternative improvements for the next 5 years is still at a stable service level, with a DS value in 2028 of 0.76 at service level (D).